Stand structure mediates the process of nutrient resorption in Chinese fir plantations during different stand developments - Ouyang, Yuanli; Chen, Minxuan; Huang, Qinxiu; Chen, Fusheng; Zhang, Cancan; Bu, Wensheng (Frontiers in Plant Science, 2025)
IntroductionNutrient resorption refers to the process of transferring nutrients from senescing organs to living organs within plants for reuse. It is a key strategy enabling plants to conserve nutrients essential for growth and development. However, how stand structure influences nutrient resorption in different organs across stand developmental stages remains unclear.MethodsIn this study, we conducted field investigations in 39 plots (20 m × 20 m) within Chinese fir plantations spanning four developmental stages, measuring nitrogen and phosphorus resorption efficiencies (NRE and PRE) in fine roots, twigs, leaves. We additionally calculated crown ratios, dead twig biomass, and relative growth rates within each plot.ResultsOur results showed that stand density and relative growth rate decreased, while crown ratios increased and dead twig biomass initially increased rapidly before gradually declining during stand development. With stand aging, nitrogen concentrations increased in all organs, whereas phosphorus concentrations varied in aboveground vs. underground organs. Leaf NRE (NREL) and absorptive/transportive root NRE (NREAR and NRETR) peaked in young forests and progressively declined with stand development. Conversely, PRE in leaves and twigs (PREL and PRET) reached maximum values in intermediate and mature forests. Trait network analysis revealed developmental stage-dependent shifts in central hub traits from NREAR to PREL and NRETR, which reflected the change of nutrient demand during stand development. These findings demonstrate aboveground-belowground synergies in nutrient resorption, with fine roots mediating nutrient acquisition to support twig ans, accounting for the mass loss correctiond leaf growth. Developmental stages exerted dual effects: positively influencing stand structure while negatively impacting organ-level nutrient resorption. Stand development and structure similarly affected aboveground resorption efficiency (REAG), whereas belowground resorption efficiency (REUG) was mainly regulated by developmental stage. Stand structure positively influenced REAG and REUG through crown ratio suppression and stand density/relative growth rate/dead twig biomass enhancement.DiscussionOur results suggest management strategies for Chinese fir plantations: phosphorus addition in mature stands versus nitrogen supplementation in other stages, coupled with either increased initial planting density in young forests or preemptive understory canopy pruning to optimize nutrient resorption - particularly in nutrient-limited environments.